PENINGKATAN KOMPETENSI SUMBER DAYA MANUSIA DALAM MENDUKUNG PELAYANAN MASYARAKAT YANG EFEKTIF DI DESA OMBO - Sulfitri Husain; Suasa Suasa; Meldi Meldi; Faradila Oktafiani; Rizky Meilani (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The improvement of human resource (HR) competencies is very important as an effort to support public services to be carried out effectively, especially in rural areas. This service aims to identify and analyze efforts to improve human resource competencies in order to enhance the quality of public services in Ombo Village, Sirenja District, Donggala Regency. The methods used include a qualitative approach with observations at the service location, interviews, and document analysis. The research results indicate that education and human resource development play a crucial role in enhancing the capabilities of village officials and public service personnel in the village. The education provided includes an understanding of the duties and functions of village government officials, with the expectation that they can manage resources, including the management and administration of village governance, as well as the basic concepts of service quality, including the rights and obligations of the community. The implementation of this program has an impact on improving service efficiency, community satisfaction, and responsiveness to the needs of residents. However, there are several challenges such as limited resources, infrastructure, and budget support that affect the sustainability of the program. Therefore, synergy between local government, stakeholders, and the community is necessary to ensure that the human resource competency enhancement program runs sustainably and provides long-term benefits for public services in Ombo Village.